Synthesis of γ‐WO3 thin films by hot wire‐CVD and investigation of its humidity sensing properties. Issue 5 (20th February 2017) - Jadkar, Vijaya; Pawbake, Amit; Waykar, Ravindra; Jadhavar, Ashok; Date, Abhijit; Late, Dattatray; Pathan, Habib; Gosavi, Suresh; Jadkar, Sandesh
Abstract : In this study, monoclinic tungsten oxide (γ‐WO3 ) have been grown in a single step using HW‐CVD method by resistively heating W filaments in a constant O2 pressure. The formation of γ‐WO3 was confirmed using low angle‐XRD and Raman spectroscopy analysis. Low angle‐XRD analysis revealed that as‐deposited WO3 film are highly crystalline and the crystallites have preferred orientation along the (002) direction. HRTEM analysis and SAED pattern also show the highly crystalline nature of WO3 with d spacing of ∼ 0.38 nm, having an orientation along the (002) direction. Surface topography investigated by SEM analysis shows the formation of a uniform and homogeneous cauliflower like morphology throughout the substrate surface without flaws and cracks. A humidity sensing device incorporating WO3 is also fabricated, which shows a maximum humidity sensitivity factor of ∼ 3954% along with a response time of ∼14 s and a recovery time of ∼25 s. The obtained results demonstrate that it is possible to synthesize WO3 in a single step by HW‐CVD method and to fabricate a humidity sensor by using it.